Development and validation of MyQUITVAPE: a health education video for quitting vaping among university students / Ching Sin Siau ... [et al.] - Siau, Ching Sin; Wee, Lei Hum; Chan, Caryn Mei Hsien; Mat Salleh, Rawaida; Phoa, Picholas Kian Ann; Fariduddin, Muhamad Nur; Ambigapathy, Subashini; Said, Zaini; Baharom, Nizam (Universiti Teknologi MARA, 2025)
The use of e-cigarettes (EC), also known as vapes, has been rising among young adults. Past studies showed a high rate of adverse events following the use of vape. However, harm perception of vape use was low. Considering this situation, there is a need for a health education programme to increase the motivation to stop vaping for university students in Malaysia. Hence, this study aimed to develop a health education programme comprising a series of short videos to educate university students on vaping harms and to increase their motivation to quit vaping. Based on prior evidence obtained from a mixed-methods study, and review of literature, Evaluation was done by 11 experts in the field. The Content Validity Index was found to be acceptable, at 0.95. The written module was copyrighted on 30 November 2023 (Notification no.: CRLY2023W05981). After that, a professional content creator was employed to create four short videos based on the script provided in the module. The video modules were created based on the script in the MyQUITVAPE module scripts. The names of the short videos were tailored to reflect their content, which focused on understanding what is vaping, the harmful effects of nicotine addiction via vaping on health, reasons for quitting vape and how to increase the motivation to do so, and sharing some skills on how to quit vaping and maintaining abstinence from vaping. Future dissemination plans of the short video will be conducted through various platforms.